Effect of embryo vitrification on the expression of brain tissue proteins in mouse offspring. (1st November 2020) - Zhu, Wenjing; Zheng, Jingxuan; Wen, Yangxing; Li, Yubin; Zhou, Canquan; Wang, Zengyan
Abstract: Vitrification is widely used in assisted reproductive technologies. However, the nervous system of vitrification offspring is of concern, and research on this is lacking. Vitrification-born mice (vitrification group), conventional in vitro fertilization-embryo transfer pregnancy-born mice (IVF group), and natural pregnancy-born mice (control group) were used to study the effects of vitrification of mouse embryos on protein levels in the brain of offspring. Proteins differentially expressed among the three groups were analyzed using proteomic methods, including two-dimensional electrophoresis, mass spectrometry, and bioinformatics analysis. Immunohistochemistry was used to verify the expression of differentially expressed proteins, such as Actb and Actg1, in each group. Twenty differentially expressed proteins in the brain tissue were identified using two-dimensional protein electrophoresis and mass spectrometry. Bioinformatics analysis revealed that these proteins were related to the development of anatomical structure, signal transduction, transport, cell differentiation, and stress response (biological processes) and the binding of molecules in vivo (molecular functions). The Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that the differentially expressed proteins were involved in 54 pathways, including phagosome, metabolic pathway, apoptosis, and cysteine and methionine metabolism. Thus, embryo vitrification may cause some changes in the mouse brain at the protein level, necessitating further safety assessment.